Multiple lines of evidence show that Phymaturus agilis Scolaro, Ibargüengoytía & Pincheira-Donoso, 2008 is a junior synonym of Phymaturus spectabilis Lobo & Quinteros, 2005 - Lobo Gaviola, Fernando Jose (2012)
Lobo and Quinteros (2005) described Phymaturus spectabilis from Río Negro Province, Argentina. The species was characterized most notably by having a brown background with a more-or-less bilaterally symmetrical pattern of bold, light tan markings, some enclosing small brown spots, on the head, limbs, body, and tail. In 2008, Scolaro et al. described P. agilis from a locality 22 km south of the type locality of P. spectabilis. It was reported to differ from P. spectabilis in its nearly uniform brown color and certain morphometric and meristic characteristics. In 2009 we collected, at the type locality of P. agilis, five adults (both sexes) with the bold pattern of P. spectabilis, and five adults (both sexes) with the uniform color of P. agilis. Subsequently, one of the females with the P. spectabilis pattern gave birth to two individuals, one of which had the pattern of P. agilis, the other with the pattern of P. spectabilis. Our analyses of specimens assignable to P. agilis and P. spectabilis detected no significant differences between individuals with the two patterns for nine morphological variables (including those used to diagnose P. agilis), with overlap in the ranges of the variables for both patterns. We therefore conclude that P. agilis is a junior synonym of P. spectabilis.